Sosialisasi Sadar Wisata Dan Pendampingan Promosi Untuk Pengembangan Agrowisata Desa Plalangan - Erdiansyah, Iqbal; Dzulkifli, Muhammad; Hariyanto, Agus; Eliyatiningsih, Eliyatiningsih (JCSE: Journal of Community Service and Empowerment, 2024)
Plalangan Village in Kalisat District is one of the agricultural villages with food crop centers targeted by The Jember Regency Government to become a tourism pilot area. Plalangan Village has natural resource potential that can be used as a tourism product, including expanses of agricultural land for food crops with semi-organic and intercropping cultivation systems, fisheries nurseries and cultivation, and a beautiful mountainous natural environment. Even though the tourism potential is very large, it has not been developed optimally by the community. So far, Pokdarwis Selayang Pandang still has a minimal role in developing tourism in Plalangan Village. This is because the human resource capacity is still low in managing tourist villages. Another problem is that there have been no promotional activities for tourist villages. The aim of this community service activity is to increase Pokdarwis' awareness of tourism potential and increase their ability to promote tourism villages. From this activities, it is hoped that there will be an increase in tourism awareness and motivation, an increase in the ability of human resources in managing village tourism potential, and the existence of promotional media for tourism villages. Keywords: promotion, tourism, villages